2021
DOI: 10.3389/fendo.2021.669507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Cumulus Cell Removal on Treatment Outcomes in Patients Undergoing In Vitro Fertilization: A Retrospective Cohort Study

Abstract: BackgroundEarly cumulus cell removal combined with early rescue intracytoplasmic sperm injection (ICSI) has been widely practiced in many in vitro fertilization (IVF) centers in China in order to avoid total fertilization failure. However, uncertainty remains whether the pregnancy and neonatal outcomes are associated with early cumulus cell removal.ObjectivesTo investigate if early cumulus cell removal alone after 4 hours co-incubation of gametes (4 h group), has detrimental effect on the pregnancy and neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…Meanwhile, early R‐ICSI was shown to be safe for the offspring. A study with large number cases was to investigate the effects of early cumulus cell removal (n = 570) on pregnancy and neonatal outcomes as compared to routine cumulus cell removal (n = 1214), and it showed that early cumulus cell removal alone was not associated with adverse pregnancy and neonatal outcomes 31 . Also, no differences in sex, birth weight, and birth defects were found between newborns delivered by conventional IVF, ICSI, or early R‐ICSI 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, early R‐ICSI was shown to be safe for the offspring. A study with large number cases was to investigate the effects of early cumulus cell removal (n = 570) on pregnancy and neonatal outcomes as compared to routine cumulus cell removal (n = 1214), and it showed that early cumulus cell removal alone was not associated with adverse pregnancy and neonatal outcomes 31 . Also, no differences in sex, birth weight, and birth defects were found between newborns delivered by conventional IVF, ICSI, or early R‐ICSI 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the early cumulus cell removal alone (4 h) had similar pregnancy outcomes compared with conventional cumulus cell removal after 20 hours of insemination (Kong et al 2021). However, the pregnancy outcomes of R-ICSI embryos in fresh cycles remains controversial.…”
Section: The Pregnancy Outcomes Of Fet In R-icsi and Icsi Groupsmentioning
confidence: 93%
“…Therefore, to prevent unfavorable effects on oocytes and related embryos from high ROS exposure, a shorter incubation of gametes has been proposed. Studies addressing the comparison between short gametes co-incubation to standard overnight IVF (16–18 h) are listed in Table 1 [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Yet in 1996, Gianaroli et al reported that a short gamete co-incubation (1 h) led to an increased rate of oocyte fertilization and embryo viability, suggesting that prolonged exposure of oocytes to elevated concentrations of sperm cells may negatively influence early embryo development [ 22 ].…”
Section: Conventional Ivf: Technical Detailsmentioning
confidence: 99%
“…In accordance, Le Bras and colleagues demonstrated that short gamete co-incubation period (2 h) leads to higher embryo quality, with a percentage of fragmentation lower than 25%, and, most importantly, to a significant increase in clinical pregnancy after a fresh embryo transfer compared to standard overnight insemination (16–18 h) [ 23 ]. Other studies reported that a shorter oocyte-spermatozoa incubation time is associated with an enhanced embryo quality and could prevent total fertilization failure (TTF) [ 24 , 25 ]. Conversely, in a prospective study, Barraud-Lange et al evaluated the effects of a short gamete co-incubation (1 h) on fertilization rate and embryo quality of sibling oocytes, showing a decreased fertilization rate and comparable embryo quality compared to the standard overnight insemination method [ 26 ].…”
Section: Conventional Ivf: Technical Detailsmentioning
confidence: 99%